Can we Make Homoeopathy like a Mathematical Science in Certainty? May be, Yes. How, When & Why? (Advancements in Homeopathic Research, 2022)
First let us know, what Dr. Hahnemann wrote about Homoeopathy. “Thus homoeopathy is a perfectly simple system of medicine, remaining always fixed in its principles as in its practice, which, like the doctrine whereon it is based, if rightly apprehended will be found to be complete (and therefore serviceable)”. (Organon of Medicine, 6th edition, Preface P.19; 1842). How is it, “a perfectly simple system of medicine (and therefore serviceable)”? Was it in 1842?
Keywords: symptoms; medicine; eruptions